Genomic characteristics of a Streptococcus suis of ST353 resulting in severe endophthalmitis with bilateral deafness - Liang Shen; Yanfei Tong; Shichao Li; Yuda Chen; Ruhan A; Zhen Li; Wenling Wang; Lijuan Yin; Jiuming Zou; Ziyong Sun; Changcheng Wu; Wenjie Tan; et al. (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Background:. Streptococcus suis (S. suis) can be transmitted to humans through exposure to pigs or consumption of raw pork and causes serious diseases. Although infection through skin abrasions is considered an important route of transmission, few studies have reported skin injuries in patients during exposure or before infection. This study explored a rare instance of intraocular infection and bilateral deafness caused by S. suis and emphasized the importance of timely diagnosis and treatment to prevent disease progression. Methods:. The diagnosis was made on the basis of clinical symptoms, imaging, molecular detection, and isolated culture methods. Drug susceptibility testing was conducted to determine the effectiveness of antibiotics. Whole-genome sequencing was used to identify the strain’s sequence type and serotype as well as the presence of pathogenicity islands (PAIs). Results:. A patient with intraocular infection and bilateral deafness was diagnosed with an S. suis infection. The infection was hypothesized to result from interspecies transmission due to the patient’s occupation and recent skin damage. The isolated strain was sensitive to ampicillin, ceftriaxone, vancomycin, linezolid, levofloxacin, and meropenem. Whole-genome sequencing revealed that the strain belonged to sequence type 353 and serotype 2, showing close similarity to strains isolated from wild boars in Chinese provinces. The strain lacked the 89 complete kb PAI but had a 33 kb PAI with high similarity, potentially indicating variable virulence. Conclusion:. This study highlights the importance of employing multiple diagnostic strategies for the timely identification and treatment of S. suis infections. The presence of a potentially less virulent strain emphasizes the need for continuous surveillance and monitoring of emerging S. suis infections, particularly in Asian countries with high-risk populations associated with the pig farming industry.